2023
DOI: 10.3389/fmicb.2023.1100590
|View full text |Cite
|
Sign up to set email alerts
|

Microbiome diversity, composition and assembly in a California citrus orchard

Abstract: The citrus root and rhizosphere microbiomes have been relatively well described in the literature, especially in the context of Huanglonbing disease. Yet questions addressing the assembly of root microbial endophytes have remained unanswered. In the above ground tree tissues, leaves and stems have been the research focus point, while flush and flower microbiomes, two important tissues in the vegetative and reproductive cycles of the tree, are not well described. In this study, the fungal and bacterial taxa in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 71 publications
(79 reference statements)
0
4
0
Order By: Relevance
“…(2022) . Similarly, Pseudomonas , Sphingomonas , and Streptomyces were identified as shared taxa in the rhizosphere, root endosphere, flower and flush of citrus in California by Xi et al. (2023) .…”
Section: Discussionmentioning
confidence: 97%
“…(2022) . Similarly, Pseudomonas , Sphingomonas , and Streptomyces were identified as shared taxa in the rhizosphere, root endosphere, flower and flush of citrus in California by Xi et al. (2023) .…”
Section: Discussionmentioning
confidence: 97%
“…The phyllosphere diversity of Bourardia ternifolia, a medicinal plant, is less than root and rhizosphere ( 61 ). Microbiome diversity analysis of California citrus orchard also revealed that the overall diversity in above-ground tissues was less than root exosphere and endosphere ( 62 ). The predominant phyla found in the different parts of P. kurrooa are also known to colonize as endophytic bacterial communities in other plants, including Arabidopsis, Maize, Tamarix, B. ternifolia, Seagrass, and Cinnamon ( 63 68 ).…”
Section: Discussionmentioning
confidence: 99%
“…Like other crops, soil microbial communities participate in root microbial assembly in citrus, as specific microbes are selected from the soil and recruited into the rhizosphere, with root exudates acting as signal molecules and nutrition sources. Citrus recruits rhizosphere microbial communities from the extensive soil biodiversity, and the microbiome is considered to play a significant role in maintaining citrus health [24][25][26][27][28][29]. An increasing number of studies, primarily utilizing amplicon-based metagenomics and also whole-genome shotgun metagenomics, have delved into the microbial communities associated with citrus [25,26,30,31].…”
Section: Introductionmentioning
confidence: 99%